Novel frequency-domain oversampling receiver for CP MC-CDMA systems - Ma, Maode (2015)
The multi-carrier code division multiple access (MC-CDMA) technique is a promising technology because it incorporates the benefits of the orthogonal frequency division multiplexing (OFDM) and the direct sequence code division multiple access (DS-CDMA) techniques. The bit error rate (BER) of the MC-CDMA system reduces more quickly than that of the OFDM system when increasing the transmission power. In this paper, we propose a novel frequency-domain oversampling (FDO) minimum mean square error (MMSE) receiver for the cyclic prefix (CP) MC-CDMA. Simulation results show that the proposed FDO based receiver for the CP MC-CDMA systems can outperform the traditional zero forcing (ZF) and MMSE equalizers in terms of BER performance for all the spreading factors (SF).